PERBEDAAN MOTIVASI BERPRESTASI AKADEMIK DITINJAU DARI GAYA ATRIBUSI PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS HKBP NOMMENSEN MEDAN (Jurnal Visi Eksakta, 2025)
This study aims to test whether there are differences in achievement motivation in terms of attributional style among students of the Faculty of Psychology, University of HKBP Nommensen. The sample in this study was 197 active students of the Faculty of Psychology, HKBP Nommensen University. The research instrument used were the achievement motivation scale and the attribution style scale. The results of the study using the ANOVA test showed that there were significant differences in achievement motivation in terms of attributional style (F= 2.75, p < 0.05).